Obtenção e caracterização de nanopartículas magnéticas inseridas em materiais carbonosos porosos a partir da decomposição do pentacarbonil ferro - Schettino Junior, Miguel Angelo (2009)
This work is concerned with the synthesis and characterization of iron oxide nanoparticles embedded into an activated carbon, giving rise to nanocomposites with magnetic properties. The samples were prepared starting from the mixture of the organometallic compound iron pentacarbonyl and the activated carbon, with various reactant ratios, under argon or ambient atmosphere. The experimental techniques used for the characterization of the products were: Mössbauer spectroscopy, X-ray diffraction - with conventional or synchrotron radiation -, X-ray photoelectron spectroscopy, scanning electron microscopy, textural analysis using nitrogen adsorption, measurements of magnetic properties, elemental analysis and thermogravimety. The results showed that the iron contents in the as prepared samples reached values up to ca. 32 wt.%. The nanoparticles were identified as iron oxides homogeneously dispersed into the activated carbon, with average crystallite sizes in the range 4-6 nm and exhibiting superparamagnetic behaviour at room temperature. The samples prepared under ambient atmosphere showed the predominance of hematite and magnetite, whereas only magnetite was detected in the samples prepared under argon atmosphere. The specific surface area and the total pore volume of the activated carbon showed a reduction of 40 and 50%, respectively, after the formation of the nanoparticles. Heat treatments carried out under inert atmosphere led to the growth of the iron oxide crystallites; the reduction of the iron oxidation state started at ca. 400?C, up to temperatures close to 700 oC. The samples heat treated at 900 oC exhibited the presence of metallic iron as the dominant phase, besides the formation of iron carbides. High-temperature X-ray diffraction experiments performed in situ during the heat treatments revealed the appearance of wüstite as an intermediate phase previous to the formation of metallic iron. The thermal expansion coefficients found for the nanocrystalline iron oxides were considerably higher than the values expected for the bulk phases, an effect associated with the large fraction of surface atoms in the nanoparticles. The results of this work showed that the followed methods of synthesis and subsequent heat treatments allow the achievement of magnetic iron-containing nanoparticles dispersed into the activated carbon matrix. The nature and the average size of these particles depend on the specific experimental conditions, such as the atmosphere of synthesis, the temperature and the time of heat treatment.